Managing woodlands for conservation and biodiversity on private land - Godfrey, T. (Cranfield University, 2008)
The concept of sustainable development has become a central and fundamental aim of governments, and increasingly corporate strategy. Conservation and biodiversity are fundamental to this agenda. Although research has assessed the conflicts between sustainable development and biodiversity conservation at global, regional and landscape levels, few authors have focused on the local scale. Where privately owned land has significant ecological value, and future site re-development is a consideration to realise full economic potential, a number of issues and potential tradeoffs arise. Indeed sustainability involves not just environmental aspects but social and economic goals. This paper draws on evidence gathered from a privately owned woodland in Hertfordshire, UK which is known to contain a population of the protected great crested newt (Triturus cristatus). A vegetation survey was carried out and geo-referenced data incorporated into a Geographical Information System (GIS). A management plan has been designed to protect and enhance the T. cristatus population and the inherent biodiversity of the woodland, as well as to contribute to social and economic sustainability. The implications of different management options and nearby development on the site are discussed and potential tradeoffs identified. This study has shown the usefulness of GIS in the display and analysis of ecological survey findings and the presentation of management options. The research has demonstrated that with the implementation of a management plan landowners can contribute to environmental, social and economic sustainability as well as creating corporate benefits. The study has highlighted a number of knowledge and research gaps that need attention, in particular the investigation of tradeoffs and issues that arise at the local scale between conservation, development and other landowner objectives. Key words: habitat management; great crested newt (Triturus cristatus); sustainable development; biodiversity; conservation; tradeoffs
Keywords: habitat management; great crested newt (Triturus cristatus); sustainable development; biodiversity; conservation; tradeoffs